Kedudukan dan Kekuatan Hukum Akta Kuasa Menjual terhadap Objek Jaminan Fidusia - Muhammad Yadi Harahap; Jihan Salsabila Najma Sari; Adinda Dara Sakinah Lubis; Aisyah Syafitri Ilham; Amanda Zahra Nasution (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The growth of financing activities in Indonesia has increased the use of fiduciary security as a legal instrument to protect creditors. In practice, besides the fiduciary security deed, a power of attorney to sell is often executed, granting authority to creditors to sell the collateral object when the debtor defaults. The existence of such a deed raises legal issues concerning its legal status in fiduciary agreements, its legal force over fiduciary collateral, and the legal protection afforded to creditors and debtors. This study aims to analyze the legal position of the power of attorney to sell in fiduciary security agreements, examine its legal force over fiduciary collateral, and identify the forms of legal protection available to the parties involved. Research findings show that the power of attorney for sale is an additional agreement, so its existence depends on the existence of the main agreement in the form of a financing contract which is the basis of the legal relationship between the parties. Data were collected through library research involving primary, secondary, and tertiary legal materials, which were analyzed qualitatively. The findings indicate that the power of attorney to sell constitutes an accessory agreement whose existence depends on the principal financing agreement. The deed has binding legal force based on Articles 1792 and 1338 of the Indonesian Civil Code and serves as a supporting instrument for the exercise of creditors’ rights over fiduciary collateral. Legal protection for creditors is reflected in the assurance of debt repayment through the collateral, while debtors are protected through their rights to information, entitlement to any surplus proceeds from the sale of collateral, and access to dispute resolution through negotiation, mediation, or court proceedings.